Hollow bicomponent parallel elastic fiber
Patent Information
- Application Number
- CN202410925925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-07-11
AI Technical Summary
该专利中纤维断裂强度只有2.8±0.2cN/dtex,且纤维纤度较高,高纤度的纤维无法满足下游市场对于低纤度的需求,当使用后拉伸调整该PET/PTT纤维的单丝纤度时,由于其纤维断裂强度过低而无法完成后拉伸,会出现毛丝、断丝现象
[0045](1)本发明的一种中空双组份并列型弹性纤维,纤维组分A部和纤维组分B部原料收缩性不同,且空心结构位置位于界面处且偏向于纤维组分A部,既能够最大限度的保留中空度,也能避免无法实现高倍拉伸的问题,实现更大的卷曲弹性;
Smart Images

Figure CN118685873B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fiber technology and relates to a hollow bicomponent parallel elastic fiber. Background Technology
[0002] Hollow fiber is a type of fiber with continuous cavities in the middle. The advantage of hollow fiber over solid fiber is that the cavities in the middle of the fiber can hold air, which has a heat-insulating function. Under the same fineness, this type of fiber has a larger volume and is therefore more fluffy. Under the same fiber volume, the fiber is lighter.
[0003] Side-by-side composite fibers are composed of two types of polymers with different shrinkage properties, exhibiting unique crimp characteristics and excellent elasticity. For example, PET / PTT bicomponent fibers are characterized by PTT playing a high shrinkage role in the fiber, while PET is rigid and virtually non-shrinking. This difference in shrinkage between PTT and PET creates a crimped structure in the fiber after heat treatment, resulting in excellent elastic elongation and elastic recovery properties.
[0004] To achieve fiber differentiation and multifunctionality, existing technologies aim to design fibers with high hollowness and excellent elasticity by combining the hollow structure characteristics with the bicomponent characteristics of fibers. For example, CN218969448U discloses a parallel hollow elastic fiber, wherein the fiber has a circular cross-section containing two cavities symmetrically spaced within the circular cross-section; the shape of the cavities is selected from circular, elliptical, or semi-circular; the circular cross-section is formed by overlapping left and right portions, each composed of different heat-shrinkable fiber-forming polymers. This parallel hollow elastic fiber has a fineness of 6.55±0.5 dtex, a breaking strength of 2.8±0.2 cN / dtex, a breaking elongation of 138±15%, a crimp elasticity of 95.0±1.0%, a crimp recovery rate of 30.5±1.5%, a hollowness of 24.0±2.0%, and a Cca value of approximately 30%. The fiber breaking strength in this patent is only 2.8±0.2 cN / dtex, and the fiber fineness is relatively high. This high fineness cannot meet the downstream market's demand for low fineness. When adjusting the fineness of the PET / PTT fiber filaments through post-stretching, the low breaking strength prevents successful post-stretching, resulting in fuzzy and broken fibers. Furthermore, while increasing the winding speed can reduce the fineness to around 3.3 dtex, it further increases the difficulty of forming pores, inevitably leading to a significant decrease in hollowness. Maintaining this type of hollow structure distribution (as described in patent CN218969448U) would be problematic. Figure 1 , 5As shown in Figure 6, it is difficult to obtain the best curling performance. That is, at low fiber density, the hollow structure of this type of bicomponent not only decreases in hollowness, but also suffers a serious loss in curling performance.
[0005] Therefore, researching a hollow bicomponent parallel elastic fiber that can achieve ideal elastic properties while ensuring high hollowness is of great significance. Summary of the Invention
[0006] The purpose of this invention is to solve the problems in the prior art and provide a hollow bicomponent parallel elastic fiber.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B, the connection between fiber component A and fiber component B is an arc segment X, the protrusion of the arc segment X faces the fiber component B, and the arc length L of the arc segment X is at least 1.2 times the diameter D of the hollow bicomponent parallel elastic fiber, denoted as the arc length multiple;
[0009] The parallel structure of the present invention can be any structure known to those skilled in the art; for example, the parallel structure can be a circular parallel structure, an elliptical parallel structure, a peanut-shaped parallel structure, a snowman-shaped parallel structure, etc.
[0010] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0011] The resin raw material corresponding to fiber component A is a low-shrinkage resin, and the resin raw material corresponding to fiber component B is a high-shrinkage resin.
[0012] Because fiber component A is a low-shrinkage resin and fiber component B is a high-shrinkage resin, the molecular chains of fiber components A and B will undergo different degrees of stress shrinkage and thermal shrinkage after stretching and orientation, resulting in permanent crimping. The greater the difference in shrinkage between fiber components A and B, the better the crimping, and thus the better the elasticity. Stretching nascent fibers can change the orientation degree of long-chain molecules in the fiber. The greater the stretching ratio of the fiber, the higher the orientation degree of fiber component A, and the greater the degree of fiber shrinkage. The orientation degree of fiber component A in nascent fibers is basically 0. In the post-stretching stage, under the action of heat and external force, the fiber is stretched and oriented, resulting in an increase in orientation degree.
[0013] Based on their shrinkage properties, resin raw materials can be divided into two categories: low-shrinkage resins and high-shrinkage resins. The shrinkage performance of resin raw materials is evaluated by the percentage decrease in their orientation degree. Resin raw materials with an orientation degree decrease of ≤8% are defined as low-shrinkage resins, while those with an orientation degree decrease of ≥10% are defined as high-shrinkage resins. Specific details are described in the terminology and definitions section below.
[0014] Unlike the hollow structure disclosed in CN218969448U, the hollow bicomponent parallel elastic fiber of this invention has its hollow structure located at the interface and biased towards fiber component A. The elasticity of the hollow bicomponent parallel elastic fiber depends on the acquisition of the crimped structure, which in turn depends on the difference in shrinkage characteristics between the two components and the degree of post-stretching of the nascent fiber. The difference in shrinkage characteristics depends on two factors: firstly, the difference in intrinsic viscosity (lower intrinsic viscosity results in lower shrinkage); and secondly, the difference in fiber type (e.g., PET has relatively lower shrinkage than PBT and PTT). Based on experimental research and comparison of results, the inventors have concluded that: if the hollow structure is placed in a low-viscosity resin during spinning, it is difficult to effectively retain the hollow structure before solidification during the spinning process; if the hollow structure is placed in a high-viscosity resin during spinning, although greater hollowness can be obtained, it will result in extremely poor fiber strength, making post-stretching impossible and thus preventing effective elasticity improvement. In this invention, the hollow structure is located at the interface, which maximizes the preservation of hollowness and avoids the problem of not being able to achieve high stretch ratio. However, to further reduce the adverse effects of the hollow structure on post-stretching, the hollow structure needs to be positioned towards fiber component A. If the hollow structure is positioned in fiber component B, or towards fiber component B, or at the center of the two-phase interface, it will affect the stretch ratio of the nascent fiber, making it impossible to achieve the target orientation, and thus failing to achieve the expected crimp elasticity, resulting in limited room for elasticity improvement. It is evident that the hollow structure and its size of fine denier fibers have a significant impact on the stretch ratio. If the hollow structure is positioned towards fiber component A, but the interface between fiber component A and fiber component B is approximately linear, or the arc length multiple is less than 1.2 times, such as 1.1 times or 1.05 times, it will also affect the stretch ratio of the nascent fiber, making it impossible to achieve the target orientation, and thus failing to achieve the expected crimp elasticity, resulting in limited room for elasticity improvement. In this invention, the interface formed by fiber component A and fiber component B is arc-shaped, while the interface in existing technologies is usually set as a uniform straight line division. Therefore, the arc length of this invention is significantly higher than that of existing technologies. Compared to existing technologies, constructing differentiated fiber left and right portions with this interface morphology results in a larger resin contact area, strengthening the interfacial bonding between fiber component A and fiber component B, enhancing resistance to external forces, and achieving a greater degree of crimp. This, in turn, leads to better spinnability and elasticity.
[0015] As a preferred technical solution:
[0016] As described above, a hollow bicomponent parallel elastic fiber has a hollow structure that intersects with an arc-shaped segment X, with the intersection points denoted as a and b. The area between a and b is an arc-shaped segment Y. The arc length S of arc segment Y is less than 20% of the arc length L, denoted as the arc length percentage. The hollow structure acts as a stress defect location within the fiber, and the arc length percentage affects the stretchability of the nascent fiber. Preferably, optimal stretchability is achieved when the arc length percentage is less than 20%.
[0017] The hollow bicomponent side-by-side elastic fiber described above has a high-shrinkage resin with an intrinsic viscosity that is more than 0.4 dL / g higher than that of the low-shrinkage resin.
[0018] When two types of resins have a high intrinsic viscosity difference, it is more beneficial to increase the fiber crimp rate of the composite fiber, thereby improving the fiber's elasticity. When the intrinsic viscosity difference is less than a limit value, the shrinkage characteristics are too small, the fiber crimp rate of the composite fiber is too small, resulting in insufficient elasticity and affecting usability. However, the intrinsic viscosity of the resin in fiber component A cannot be reduced indefinitely to increase the intrinsic viscosity difference, otherwise it will lead to an excessively small equivalent circle diameter of the hollow structure and insufficient spinnability; similarly, the intrinsic viscosity of the resin in fiber component B cannot be increased indefinitely, otherwise spinnability will be insufficient.
[0019] The hollow bicomponent side-by-side elastic fiber described above has a high-shrinkage resin of PTT resin with an intrinsic viscosity of 1.02 to 1.3 dL / g and a low-shrinkage resin of PET resin with an intrinsic viscosity of 0.45 to 0.55 dL / g.
[0020] The hollow bicomponent side-by-side elastic fiber described above has a high-shrinkage resin of PTT resin with an intrinsic viscosity of 1.25 to 1.3 dL / g and a low-shrinkage resin of PTT resin with an intrinsic viscosity of 0.85 to 0.96 dL / g.
[0021] The crimping properties of fibers are influenced by the shrinkage capacity of two types of resins on parallel elastic fibers after stress relief. Selecting two resin raw materials that meet the requirements of both low-shrinkage and high-shrinkage resins can achieve the objectives of this invention. The difference in shrinkage characteristics depends on both the intrinsic viscosity difference of the two components and the difference in the type of fiber. When polymers of the same type have different orientation reduction ratios at different viscosities, for example, when the intrinsic viscosity of PTT resin is 1.25 dL / g, the orientation reduction ratio is 10%, meeting the requirements of high-shrinkage resin; when the intrinsic viscosity of PTT resin is 0.85 dL / g, the orientation reduction ratio is 5%, meeting the requirements of low-shrinkage resin.
[0022] The hollow bicomponent side-by-side elastic fiber described above has a low-shrinkage resin to high-shrinkage resin mass ratio of 60:40 to 50:50.
[0023] The hollow bicomponent parallel elastic fiber described above has an orientation degree of 0.05 to 0.17 for the low-shrinkage resin component.
[0024] The hollow bicomponent parallel elastic fiber described above has a diameter ≤50μm, a hollowness ≥10%, and a crimp elongation (Cca) ≥45%.
[0025] The hollow bicomponent parallel elastic fiber described above has a diameter of 15–50 μm, a hollowness of 10–30%, and a crimp elongation of 45–62%.
[0026] When the fiber diameter is less than 15μm, it is found that the excessively fine fiber diameter seriously affects the Cca value; when the fiber diameter is greater than 50μm, the fiber monofilament is too thick, which will result in a poor hand feel of the fabric.
[0027] High or medium porosity is a goal pursued by those skilled in the art. A porosity of at least 10% can achieve ideal thermal insulation and other functional properties. The size of porosity is indirectly affected by the fiber elasticity requirements, which in turn limits the material viscosity, fiber A and B components and structure, etc., thus making it impossible for the porosity to be infinitely large under the condition of spinnability. The maximum porosity obtained by this invention is 30%.
[0028] The method for preparing a hollow bicomponent side-by-side elastic fiber as described above includes the following steps:
[0029] (1) Preparation of raw materials:
[0030] The resin raw material corresponding to fiber component A: low-shrinkage resin;
[0031] Resin raw material corresponding to fiber component B; high-shrinkage resin;
[0032] The mass ratio of low-shrinkage resin to high-shrinkage resin is 60:40 to 50:50.
[0033] (2) Drying:
[0034] The resin raw material corresponding to fiber component A is first pre-crystallized, and then dried at a drying temperature of 150-185℃ until the moisture content meets the requirements for spinning; the resin raw material corresponding to fiber component B is directly dried at a drying temperature of 120-140℃ until the moisture content meets the requirements for spinning.
[0035] (3) Spinning:
[0036] The resin raw materials corresponding to fiber component A and fiber component B enter the same spinning box from different screws, melt pipes and metering pumps, and are then distributed by the assembly to each spinneret hole on the same spinneret plate. The two components are distributed to each spinneret hole for melt extrusion.
[0037] Among them, the resin raw material corresponding to fiber component A is melt-extruded in the temperature range of 270 to 280°C, and the resin raw material corresponding to fiber component B is melt-extruded in the temperature range of 250 to 265°C.
[0038] The spinneret is hollow and designed to achieve the target fiber cross-sectional area. The spinneret design allows the two component raw materials to partially merge upon entering the spinneret orifice and then separate again upon exiting, forming a porous structure, thus creating the hollow structure. Designing spinneret structures based on specific fiber cross-sectional requirements is existing technology and will not be elaborated upon here.
[0039] (4) Cooling and shaping:
[0040] After the two melts are extruded through the spinneret, they are sequentially cooled, shaped, oiled, heated, stretched, set, and wound to form hollow bicomponent parallel elastic fibers.
[0041] The cooling system employs side-blowing or ring-blowing cooling methods, with a cooling temperature range of 18–25℃ and a cooling air velocity set between 0.35 and 0.60 m / s.
[0042] Oiling is performed using an oiler to increase the lubrication and antistatic properties of the fibers, so that the fibers can be used smoothly in subsequent processes.
[0043] During the stretching process, the hot roller is heated to 75-170°C to ensure that the fiber is fully stretched, thereby achieving the physical properties required for subsequent use and generating sufficient crimp to form adequate crimp elasticity.
[0044] Beneficial effects:
[0045] (1) A hollow bicomponent parallel elastic fiber of the present invention has different shrinkage properties of fiber component A and fiber component B, and the hollow structure is located at the interface and biased towards fiber component A. This can maximize the retention of hollowness and avoid the problem of not being able to achieve high stretching, thus achieving greater crimp elasticity.
[0046] (2) The hollow bicomponent parallel elastic fiber of the present invention can have excellent elastic properties while ensuring high hollowness. Attached Figure Description
[0047] Figure 1A schematic diagram of hollow bicomponent parallel elastic fibers;
[0048] Figure 2 A schematic diagram of hollow bicomponent parallel elastic fibers;
[0049] Figure 3 The image shows the hollow bicomponent side-by-side elastic fibers of Example 1 under a microscope.
[0050] Figure 4 for Figure 3 A magnified view of a portion of the image;
[0051] Figure 5 The image shows the hollow bicomponent side-by-side elastic fibers of Example 2 under a microscope.
[0052] Figure 6 for Figure 5 A magnified view of a portion of the image;
[0053] Figure 7 This is a microscopic image of the hollow bicomponent side-by-side elastic fibers of Comparative Example 2.
[0054] Figure 8 for Figure 7 A magnified view of a portion of the image. Detailed Implementation
[0055] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0056] Terms and definitions in this invention:
[0057] Low shrinkage resin: Resin raw materials with an orientation degree decrease of ≤8% are defined as low shrinkage resin;
[0058] High shrinkage resin: Resin raw materials with an orientation degree decrease of ≥10% are defined as high shrinkage resin;
[0059] The resin raw material was prepared into fibrous samples to evaluate the proportion of orientation degree reduction. The preparation of fibrous samples: The resin was made into fiber samples using the FDY process to evaluate the shrinkage performance of the resin. The spinning speed of the nascent fiber was controlled at 1000 m / min and the temperature at 75℃, and the subsequent stretching speed was 4000 m / min and the temperature at 150℃ to obtain fiber samples with a denier of 75D. The orientation degree I of the fiber sample was measured. The orientation degree II was measured after the fiber sample was treated at 100℃ for 1 h. The proportion of orientation degree reduction of the resin raw material = (orientation degree I - orientation degree II) / orientation degree I × 100%.
[0060] The test methods involved in the performance indicators in the embodiments and comparative examples of this invention are as follows:
[0061] (1) Intrinsic viscosity: According to the capillary viscometer method in 5.1.1 of GB / T 14190-2017 "Test Method for Fiber Grade Polyester (PET) Slices", the intrinsic viscosity of 5 PET and PTT resin raw materials was measured respectively. The solvent used was phenol / tetrachloroethane with a mass ratio of 1:1.
[0062] (2) Fiber diameter, arc length multiple, and arc length ratio: The relevant dimensions of the fibers were measured using a microscope. Twenty fiber cross-sections were selected, and the marked fiber diameter Di (i = 1~20), the interface length Li (i = 1~20) formed by fiber components A and B, and the contact length Si (i = 1~20) of the hollow structure at the two-phase interface were measured according to methods 7.3 and 7.5 in FZT 50002-2013. Li / Di and Si / Li (i = 1~20) were calculated respectively, and the average values (∑Li / Di) / 20 and (∑Si / Li) / 20 were statistically analyzed. The measurement method can be found in FZT 50002-2013.
[0063] (3) Hollowness: The hollowness of the fiber was determined according to the method in 7.6 of FZT 50002-2013.
[0064] (4) Fiber shrinkage elongation (Cca): The specific test steps are as follows:
[0065] ① Test the linear density of the fiber. Based on the measured linear density, determine the number of turns of the fiber according to the following formula: number of turns = 2500 × 0.9 / linear density. Wrap the fiber and tie knots at the beginning and end of the fiber bundle.
[0066] ② Remove the wound fiber, then add an initial load of 7.5g to the bottom of the fiber bundle, suspend the filament on the rack, put the rack in a 120℃ oven for heat treatment for 30 minutes, remove the rack from the oven, cool the filament to room temperature, and measure its length Ca after 2 hours.
[0067] ③ Gently add another 500g load, balance for 45 seconds, and then measure the length La;
[0068] ④ Calculate the Cca value: Cca = (La - Ca) / La × 100, where Ca and La are accurate to 1 mm;
[0069] (5) Orientation degree (birefringence): The birefringence of the fiber was determined according to FZ / T 01057.9-2012. Using a polarizing optical microscope, the refractive index of the refractive liquid was continuously adjusted until the Beck line of the resin in part A in the field of view disappeared. At this time, the refractive index of the refractive liquid was the refractive index parallel to the fiber direction. Then, the stage was rotated 90° and the refractive index of the refractive liquid was continuously adjusted until the Beck line of the resin in part A in the field of view disappeared. At this time, the refractive index of the refractive liquid was the refractive index perpendicular to the fiber direction. The difference between the two refractive indices Δn (birefringence) was used to characterize the orientation degree value.
[0070] The stretching conditions set in the following examples and comparative examples are typical and ideal stretching conditions. When stretched under the corresponding stretching conditions, no fuzzing or breakage of the fibers occurred.
[0071] Example 1
[0072] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0073] The resin raw material corresponding to fiber component A is PET resin with an intrinsic viscosity of 0.5 dL / g. The measured decrease in orientation degree is 5.4%, which is a low shrinkage resin.
[0074] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.15 dL / g. The measured decrease in orientation degree is 16.5%, which is a high shrinkage resin.
[0075] The mass ratio of low-shrinkage resin to high-shrinkage resin is 60:40;
[0076] like Figure 1 As shown, the connection between fiber component A and fiber component B is an arc segment X. The protrusion of arc segment X faces fiber component B. The arc length L of arc segment X is 1.3 times the diameter D of the hollow bicomponent parallel elastic fiber, which is denoted as the arc length multiple.
[0077] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0078] like Figure 2 As shown, the hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 15% of the arc length L, and is denoted as the arc length percentage.
[0079] The orientation degree of the low-shrinkage resin portion in the hollow bicomponent parallel elastic fiber is 0.17;
[0080] like Figure 3 , 4As shown, the hollow bicomponent parallel elastic fiber has a diameter of 30 μm, a hollowness of 22%, and a crimp elongation of 60%.
[0081] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0082] The resin raw material corresponding to fiber component A has the following characteristics: pre-crystallization temperature of 185℃, drying temperature of 150℃, drying time of 8h, spinning temperature of 275℃, and melting temperature of 270℃.
[0083] The resin raw material corresponding to fiber component B: drying temperature 120℃, drying time 8h, spinning temperature 265℃, melting temperature 250℃;
[0084] The spinning box temperature is 274℃, the cooling method is ring blowing cooling, the cooling temperature is 18℃, the cooling wind speed is 0.56m / s, the hot roller temperature during drawing is 90℃, the drawing ratio is 3.7 times, and the setting temperature is 160℃.
[0085] Comparative Example 1
[0086] A hollow bicomponent parallel elastic fiber is basically the same as in Example 1, except that: the arc length L of the arc segment X is 1.15 times the diameter D of the hollow bicomponent parallel elastic fiber, and the orientation degree of the low-shrinkage resin portion in the hollow bicomponent parallel elastic fiber is 0.03.
[0087] The hollow bicomponent parallel elastic fiber has a diameter of 30 μm, a hollowness of 25%, and a crimp elongation of 30%.
[0088] Comparing Comparative Example 1 and Example 1, it can be found that the shrinkage elongation of Comparative Example 1 is significantly reduced. This is because the arc length multiple is too small, which leads to a smaller resin contact area in the hollow bicomponent parallel elastic fiber. The bonding force between the bicomponent resins is weakened, and the hollow structure is more likely to become the failure point of fiber tensile fracture. The fiber is prone to fuzzy breakage when stretched and oriented, thus failing to achieve a higher draw ratio and a higher degree of orientation of the low-shrinkage resin part, ultimately resulting in a poorer shrinkage elongation.
[0089] Comparative Example 2
[0090] A hollow bicomponent parallel elastic fiber is basically the same as in Example 1, except that the hollow structure of the hollow bicomponent parallel elastic fiber is biased towards fiber component B, and the orientation degree of the low-shrinkage resin portion of the hollow bicomponent parallel elastic fiber is 0.03.
[0091] like Figure 7 , 8As shown, the hollow bicomponent parallel elastic fiber has a diameter of 30 μm, a hollowness of 28%, and a crimp elongation of 30%.
[0092] Comparing Comparative Example 2 and Example 1, it can be found that when Comparative Example 2 is spun, the hollow structure is set in the high viscosity resin. Although it can obtain a greater degree of hollowness, it will result in extremely poor fiber strength and make it impossible to achieve post-stretching, thus failing to obtain the target orientation degree and failing to achieve the expected crimp elasticity. Ultimately, this leads to a significant decrease in the crimp elongation.
[0093] Example 2
[0094] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0095] The resin raw material corresponding to fiber component A is PET resin with an intrinsic viscosity of 0.5 dL / g. The measured decrease in orientation degree is 5.4%, which is a low shrinkage resin.
[0096] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.15 dL / g. The measured decrease in orientation degree is 16.5%, which is a high shrinkage resin.
[0097] The mass ratio of low-shrinkage resin to high-shrinkage resin is 60:40;
[0098] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.3 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0099] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0100] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 35% of the arc length L, and is denoted as the arc length percentage.
[0101] The orientation degree of the low-shrinkage resin portion in the hollow bicomponent parallel elastic fiber is 0.06;
[0102] like Figure 5 , 6 As shown, the hollow bicomponent parallel elastic fiber has a diameter of 30 μm, a hollowness of 17%, and a crimp elongation of 46%.
[0103] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0104] The resin raw material corresponding to fiber component A has the following characteristics: pre-crystallization temperature of 185℃, drying temperature of 150℃, drying time of 8h, spinning temperature of 275℃, and melting temperature of 270℃.
[0105] The resin raw material corresponding to fiber component B: drying temperature 120℃, drying time 8h, spinning temperature 265℃, melting temperature 250℃;
[0106] The spinning box temperature is 274℃, the cooling method is ring blowing cooling, the cooling temperature is 18℃, the cooling wind speed is 0.56m / s, the hot roller temperature during drawing is 90℃, the drawing ratio is 3 times, and the setting temperature is 160℃.
[0107] Example 3
[0108] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0109] The resin raw material corresponding to fiber component A is PET resin with an intrinsic viscosity of 0.55 dL / g. The measured decrease in orientation degree is 5.8%, which is a low shrinkage resin.
[0110] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.3 dL / g. The measured decrease in orientation degree is 24.8%, which is a high shrinkage resin.
[0111] The mass ratio of low-shrinkage resin to high-shrinkage resin is 50:50;
[0112] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.24 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0113] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0114] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 18% of the arc length L, and is denoted as the arc length percentage.
[0115] The orientation degree of the low-shrinkage resin portion in the hollow bicomponent parallel elastic fiber is 0.13;
[0116] The hollow bicomponent side-by-side elastic fiber has a diameter of 40 μm, a hollowness of 10%, and a crimp elongation of 57%.
[0117] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0118] The resin raw materials corresponding to fiber component A are: pre-crystallization temperature of 185℃, drying temperature of 180℃, drying time of 6.25h, spinning temperature of 275℃, and melting temperature of 275℃.
[0119] The resin raw material corresponding to fiber component B: drying temperature 130℃, drying time 7h, spinning temperature 263℃, melting temperature 260℃;
[0120] The spinning box temperature is 274℃, the cooling method is ring blowing cooling, the cooling temperature is 22℃, the cooling wind speed is 0.4m / s, the hot roller temperature during drawing is 85℃, the drawing ratio is 3.5 times, and the setting temperature is 160℃.
[0121] Example 4
[0122] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0123] The resin raw material corresponding to fiber component A is PET resin with an intrinsic viscosity of 0.45 dL / g. The measured decrease in orientation degree is 5%, which is a low shrinkage resin.
[0124] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.02 dL / g. The measured decrease in orientation degree is 10%, which is a high shrinkage resin.
[0125] The mass ratio of low-shrinkage resin to high-shrinkage resin is 55:45;
[0126] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.2 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0127] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0128] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 19% of the arc length L, and is denoted as the arc length percentage.
[0129] The orientation degree of the low-shrinkage resin portion in the hollow bicomponent parallel elastic fiber is 0.1;
[0130] The hollow bicomponent side-by-side elastic fiber has a diameter of 50 μm, a hollowness of 15%, and a crimp elongation of 50%.
[0131] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0132] The resin raw material corresponding to fiber component A has the following characteristics: pre-crystallization temperature is 185℃, drying temperature is 185℃, drying time is 6h, spinning temperature is 275℃, and melting temperature is 280℃.
[0133] The resin raw material corresponding to fiber component B: drying temperature 140℃, drying time 6h, spinning temperature 265℃, melting temperature 265℃;
[0134] The spinning box temperature is 274℃, the cooling method is side blowing cooling, the cooling temperature is 25℃, the cooling wind speed is 0.35m / s, the hot roller temperature during drawing is 75℃, the drawing ratio is 3.3 times, and the setting temperature is 160℃.
[0135] Example 5
[0136] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0137] The resin raw material corresponding to fiber component A is PET resin with an intrinsic viscosity of 0.5 dL / g. The measured decrease in orientation degree is 5.4%, which is a low shrinkage resin.
[0138] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.15 dL / g. The measured decrease in orientation degree is 16.5%, which is a high shrinkage resin.
[0139] The mass ratio of low-shrinkage resin to high-shrinkage resin is 60:40;
[0140] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.5 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0141] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0142] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 30% of the arc length L, and is denoted as the arc length percentage.
[0143] The orientation degree of the low-shrinkage resin portion in the hollow bicomponent parallel elastic fiber is 0.07;
[0144] The hollow bicomponent side-by-side elastic fiber has a diameter of 30 μm, a hollowness of 20%, and a crimp elongation of 47%.
[0145] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0146] The resin raw material corresponding to fiber component A has the following characteristics: pre-crystallization temperature of 185℃, drying temperature of 160℃, drying time of 8h, spinning temperature of 275℃, and melting temperature of 275℃.
[0147] The resin raw material corresponding to fiber component B: drying temperature 120℃, drying time 8h, spinning temperature 265℃, melting temperature 250℃;
[0148] The spinning box temperature is 274℃, the cooling method is a cooling temperature of 18℃, the cooling wind speed is 0.56m / s, the hot roller temperature during drawing is 90℃, the drawing ratio is 3.1 times, and the setting temperature is 160℃.
[0149] Example 6
[0150] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0151] The resin raw material corresponding to fiber component A is PTT resin with an intrinsic viscosity of 0.85 dL / g. The measured decrease in orientation degree is 6.5%, which is a low shrinkage resin.
[0152] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.25 dL / g. The measured decrease in orientation degree is 22.1%, which is a high shrinkage resin.
[0153] The mass ratio of low-shrinkage resin to high-shrinkage resin is 54:46;
[0154] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.22 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0155] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0156] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 20% of the arc length L, and is denoted as the arc length percentage.
[0157] The orientation degree of the low-shrinkage resin component in the hollow bicomponent side-by-side elastic fiber is 0.09;
[0158] The diameter of the hollow bicomponent side-by-side elastic fiber is 50 μm, the hollowness is 10%, and the crimp elongation is 52%.
[0159] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0160] The resin raw materials corresponding to fiber component A are: pre-crystallization temperature of 150℃, drying temperature of 155℃, drying time of 7.5h, spinning temperature of 255℃, and melting temperature of 272℃.
[0161] The resin raw material corresponding to fiber component B: drying temperature 125℃, drying time 7.5h, spinning temperature 263℃, melting temperature 252℃;
[0162] The spinning box temperature is 265℃, the cooling method is ring blowing cooling, the cooling temperature is 19℃, the cooling wind speed is 0.55m / s, the hot roller temperature during drawing is 100℃, the drawing ratio is 3.1 times, and the setting temperature is 160℃.
[0163] Example 7
[0164] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0165] The resin raw material corresponding to fiber component A is PTT resin with an intrinsic viscosity of 0.9 dL / g. The measured decrease in orientation degree is 7.3%, which is a low shrinkage resin.
[0166] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.28 dL / g. The measured decrease in orientation degree is 23.6%, which is a high shrinkage resin.
[0167] The mass ratio of low-shrinkage resin to high-shrinkage resin is 56:44;
[0168] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.25 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0169] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0170] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 18% of the arc length L, and is denoted as the arc length percentage.
[0171] The orientation degree of the low-shrinkage resin component in the hollow bicomponent side-by-side elastic fiber is 0.13;
[0172] The diameter of the hollow bicomponent side-by-side elastic fiber is 25 μm, the hollowness is 15%, and the crimp elongation is 53%.
[0173] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0174] The resin raw materials corresponding to fiber component A have the following characteristics: pre-crystallization temperature of 150℃, drying temperature of 165℃, drying time of 6.75h, spinning temperature of 255℃, and melting temperature of 274℃.
[0175] The resin raw material corresponding to fiber component B: drying temperature 130℃, drying time 7h, spinning temperature 265℃, melting temperature 256℃;
[0176] The spinning box temperature is 265℃, the cooling method is side blowing cooling, the cooling temperature is 20℃, the cooling wind speed is 0.5m / s, the hot roller temperature during drawing is 120℃, the drawing ratio is 3.4 times, and the setting temperature is 160℃.
[0177] Example 8
[0178] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0179] The resin raw material corresponding to fiber component A is PTT resin with an intrinsic viscosity of 0.96 dL / g. The measured decrease in orientation degree is 8.2%, which is a low shrinkage resin.
[0180] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.3 dL / g. The measured decrease in orientation degree is 24.8%, which is a high shrinkage resin.
[0181] The mass ratio of low-shrinkage resin to high-shrinkage resin is 58:42;
[0182] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.28 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0183] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0184] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 16% of the arc length L, and is denoted as the arc length percentage.
[0185] The orientation degree of the low-shrinkage resin component in the hollow bicomponent side-by-side elastic fiber is 0.17;
[0186] The diameter of the hollow bicomponent side-by-side elastic fiber is 10 μm, the hollowness is 22%, and the crimp elongation is 62%.
[0187] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0188] The resin raw material corresponding to fiber component A has the following characteristics: pre-crystallization temperature of 150℃, drying temperature of 170℃, drying time of 7h, spinning temperature of 260℃, and melting temperature of 276℃.
[0189] The resin raw material corresponding to fiber component B has the following characteristics: drying temperature of 135℃, drying time of 6.5h, spinning temperature of 265℃, and melting temperature of 260℃.
[0190] The spinning box temperature is 265℃, the cooling method is ring blowing cooling, the cooling temperature is 21℃, the cooling wind speed is 0.45m / s, the hot roller temperature during drawing is 170℃, the drawing ratio is 3.6 times, and the setting temperature is 160℃.
[0191] Example 9
[0192] A hollow bicomponent parallel elastic fiber, wherein the cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B;
[0193] The resin raw material corresponding to fiber component A is PTT resin with an intrinsic viscosity of 0.85 dL / g. The measured decrease in orientation degree is 6.5%, which is a low shrinkage resin.
[0194] The resin raw material corresponding to fiber component B is PTT resin with an intrinsic viscosity of 1.25 dL / g. The measured decrease in orientation degree is 22.1%, which is a high shrinkage resin.
[0195] The mass ratio of low-shrinkage resin to high-shrinkage resin is 54:46;
[0196] The connection between fiber component A and fiber component B is an arc-shaped segment X. The protrusion of arc-shaped segment X faces fiber component B. The arc length L of arc-shaped segment X is 1.22 times the diameter D of the hollow bicomponent parallel elastic fiber, and is denoted as the arc length multiple.
[0197] The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A;
[0198] The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y accounts for 40% of the arc length L, and is denoted as the arc length percentage.
[0199] The orientation degree of the low-shrinkage resin component in the hollow bicomponent side-by-side elastic fiber is 0.05;
[0200] The diameter of the hollow bicomponent side-by-side elastic fiber is 50 μm, the hollowness is 20%, and the crimp elongation is 45%.
[0201] The preparation process parameters for the above-mentioned hollow bicomponent side-by-side elastic fibers are as follows:
[0202] The resin raw materials corresponding to fiber component A are: pre-crystallization temperature of 150℃, drying temperature of 155℃, drying time of 7.5h, spinning temperature of 255℃, and melting temperature of 272℃.
[0203] The resin raw material corresponding to fiber component B: drying temperature 125℃, drying time 7.5h, spinning temperature 263℃, melting temperature 252℃;
[0204] The spinning box temperature is 265℃, the cooling method is ring blowing cooling, the cooling temperature is 19℃, the cooling wind speed is 0.55m / s, the hot roller temperature during drawing is 100℃, the drawing ratio is 2.8 times, and the setting temperature is 160℃.
Claims
1. A hollow bicomponent parallel elastic fiber, characterized in that: The cross-section of the hollow bicomponent parallel elastic fiber is divided into fiber component A and fiber component B. The connection between fiber component A and fiber component B is an arc segment X. The protrusion of arc segment X faces fiber component B. The arc length L of arc segment X is at least 1.2 times the diameter D of the hollow bicomponent parallel elastic fiber. The hollow structure of hollow bicomponent parallel elastic fibers is biased towards fiber component A; The hollow structure of the hollow bicomponent parallel elastic fiber intersects with the arc segment X, and the intersection points are denoted as a and b. The arc segment Y is between a and b. The arc length S of the arc segment Y is less than 20% of the arc length L. The resin raw material corresponding to fiber component A is a low-shrinkage resin, and the resin raw material corresponding to fiber component B is a high-shrinkage resin. The intrinsic viscosity of the high-shrinkage resin is more than 0.4 dL / g higher than that of the low-shrinkage resin. The high-shrinkage resin is PTT resin with an intrinsic viscosity of 1.02~1.3 dL / g, and the low-shrinkage resin is PET resin with an intrinsic viscosity of 0.45~0.55 dL / g; or, the high-shrinkage resin is PTT resin with an intrinsic viscosity of 1.25~1.3 dL / g, and the low-shrinkage resin is PTT resin with an intrinsic viscosity of 0.85~0.96 dL / g. The diameter of the hollow bicomponent parallel elastic fiber is 15~50μm, the hollowness is 10~30%, and the crimp elongation is 45~62%.
2. The hollow bicomponent parallel elastic fiber according to claim 1, characterized in that, The mass ratio of low-shrinkage resin to high-shrinkage resin is 60:40~50:
50.
3. The hollow bicomponent parallel elastic fiber according to claim 1, characterized in that, The orientation degree of the low-shrinkage resin component in hollow bicomponent side-by-side elastic fibers is 0.05~0.17.
Citation Information
Patent Citations
Parallel hollow elastic fiber
CN218969448U
Self-crimping far-infrared hollow composite filament and manufacturing method thereof
CN109137098A
Composite elastic fiber and preparation method thereof
CN118241338A
Polytrimethylene terephthalate hollow composite staple fibers and process for producing same
CN1768171A